1993
DOI: 10.1046/j.1524-475x.1993.10305.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of collagen synthesis and messenger RNA levels in normal and hypertrophic scar fibroblasts in vitro by interferon alfa‐2b

Abstract: Hypertrophic scars, which commonly occur after thermal and traumatic injury of the skin, are a fibroproliferative disorder of the dermal matrix wherein components of the inflammatory process, including the fibrotic growth factor, transforming growth factor-beta, appear to activate dormant fibroblasts leading to cellular proliferation and excessive matrix synthesis. To investigate the potential beneficial role and mechanism of interferon alfa-2b in controlling excessive collagen production in hypertrophic scar,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…(10)(11)(12)(13) The results of our previous studies also showed that total collagen synthesis and mRNA expression for fibronectin are reduced in response to IFN-a2b in dermal fibroblasts. (21,22) As our findings and those of others (10)(11)(12)(13) suggest that these cytokines can be used as therapeutic agents to treat FPD, the expression of collagenase, as the other side of the equation involved in collagen metabolism, in response to these cytokines needs to be investigated. Duncan and Berman (27) showed an increase in collagenase activity in conditioned medium after treatment with either IFN-a or IFN-g.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…(10)(11)(12)(13) The results of our previous studies also showed that total collagen synthesis and mRNA expression for fibronectin are reduced in response to IFN-a2b in dermal fibroblasts. (21,22) As our findings and those of others (10)(11)(12)(13) suggest that these cytokines can be used as therapeutic agents to treat FPD, the expression of collagenase, as the other side of the equation involved in collagen metabolism, in response to these cytokines needs to be investigated. Duncan and Berman (27) showed an increase in collagenase activity in conditioned medium after treatment with either IFN-a or IFN-g.…”
Section: Discussionmentioning
confidence: 75%
“…The response of postburn HSc fibroblasts to these cytokines appears similar to that of normal dermal fibroblasts obtained from the same patient. (20,21) We have also provided evidence that IFN-a2b significantly decreases the expression of fibronectin mRNA in human HSc and normal dermal fibroblasts. (21,22) These findings and those of others (10)(11)(12)(13) suggest that these cytokines can be used as therapeutic agents to normalize the accumulation of collagen in FPD.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations